Growth effects of botulinum toxin type A injected unilaterally into the masseter muscle of developing rats - Park, Chanyoung; Park, Kitae; Kim, Jiyeon (Journal of Zhejiang University. B. Science, 2015)
Objective： To evaluate the effects of botulinum toxin type A （BTX-A） on mandible skeletal development by inducing muscle hypofunction. Methods： Four-week-old Sprague-Dawley rats （n=60） were divided into three groups： Group 1 animals served as controls and were injected with saline; Group 2 animals were injected unilaterally with BTX-A （the contralateral side was injected with saline）; and Group 3 animals were injected bilaterally with BTX-A. In Group 2, the saline-injected side was designated the control side （Group 2-1）, whereas the BTX-A-injected side was designated the experimental side （Group 2-2）. After four weeks, the animals were sacrificed, dry skulls were prepared, and mandibles were measured. Results： In the unilateral group, the experimental side （Group 2-2） had reduced di- mensions for all mandible measurements compared with the control side （Group 2-1）, suggesting a local effect of BTX-A on mandible growth, likely due to muscle reduction. Conclusions： Localized BTX-A injection induced a change in craniofacial growth, and the skeletal effect was unilateral despite both sides of the mandible functioning as one unit.